Endovascular Treatment of Patients with Ruptured Intracranial Aneurysms: A Series of 468 Patients Treated Over a 14-Year Period. Issue 1 (28th March 2022) - Hulscher, Franny; Mine, Benjamin; Elens, Stéphanie; Bonnet, Thomas; Suarez, Juan Vazquez; Lubicz, Boris
Purpose: Non-traumatic subarachnoid hemorrhage (SAH) is an emergency usually caused by the rupture of a saccular intracranial aneurysm. Endovascular treatment (EVT) is now considered as the first therapeutic option. The aim of our study is to evaluate, over a 14-year period in a single center, the result of EVT of ruptured intracranial aneurysms. Methods: From the retrospective analysis of our prospectively maintained database, we collected data of 457 patients successfully treated by endovascular approach for a SAH. Descriptive statistics and percentages were used to report clinical and anatomical outcomes, procedure-related complications, post procedural events, morbidity and mortality. Results: EVT was unsuccessful in eleven patients but effective in 457 patients with two patients who experienced a rebleeding (0.4%). In 6.3% of cases, a second EVT was necessary. The final aneurysm occlusion was complete (65.7%), with a neck remnant (28.2%) or incomplete (6.1%). Procedure-related complications occurred in 5.9% of patients and were associated with five clinical worsening and one death. Overall EVT-related morbidity and mortality were thus of 1.3% and 0.4% respectively. At discharge, 71% of patients had a good recovery (mRS 0–2), 11.2% had a poor outcome (mRS 3–5), and 17.8% died. Conclusion: This study seems to prove that high-volume centers with experienced interventional neuroradiologists carry low rates of technical failure and complication from EVT of ruptured intracranial aneurysm.